PENGARUH BAGI HASIL PADA PRODUK TABUNGAN MUDHARABAH TERHADAP MINAT MENABUNG NASABAH DI BANK SYARIAH INDONESIA KCP KM 6 PALEMBANG - Siti Novira Putricia; Choiriyah Choiriyah; Muharir Muharir (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
In Indonesia, the majority are Muslims, so the demand for banks that operate in accordance with sharia has begun to emerge. This study aims to find out how the effect of profit sharing for mudharabah savings products on the interest in saving customers of Bank Syariah Indonesia Km 6 Palembang. The data collection technique in this study used a questionnaire/questionnaire with a population of several mudharabah savings customers. The research method used is simple regression analysis using SPSS software. The results obtained indicate that the profit sharing variable in the mudharabah savings product has a significant effect on the customer's interest in saving.